Maintaining Playground Relationships Through Music During a Pandemic: An Action Research Inquiry (LEARNing Landscapes, 2024)
The COVID-19 pandemic’s restrictions for schools and playgrounds threatened children’s social and emotional wellbeing. In response, Grade 4/5 students created music-based activities through action research to sustain playground interactions. This study explored the crucial yet fragile playground relationships and the children’s determination to maintain them. Findings indicate that the student‑initiated projects were not only a medium for self-expression and maintaining friendships, but also served as an important tool for reinforcing the inherent social fabric of the playground setting. Notably, this study underscores the significance of collaborative learning, interpersonal skill development, and intrinsic motivation in fostering social skills and enhancing self-confidence.
Keywords: Covid-19; pandemic; maintenance behaviours; peer relations; music education; social development